2021
DOI: 10.32604/or.2022.03550
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA LINC01124 activates hepatocellular carcinoma cell proliferation, migration, and invasion by absorbing microRNA-1247-5p and overexpressing FOXO3

Abstract: Long intergenic non-protein coding RNA 1124 (LINC01124) has been identified as an important regulator of non-small-cell lung cancer. However, the expression and detailed role of LINC01124 in hepatocellular carcinoma (HCC) remain unestablished to date. Therefore, this study aimed to elucidate the role of LINC01124 in the aggressiveness of HCC cells and identify the underlying regulatory mechanism. Quantitative reverse transcriptase-polymerase chain reaction was performed to measure the expression of LINC01124 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Another study revealed that LINC01977 accelerated LIHC progression by inhibiting Notch2 ubiquitination and depletion, suggesting that LINC01977 could be a potential biomarker and therapeutic target for LIHC patients 63 . Similarly, Sun et al indicated that LINC01124 played a tumor-promoting role in LIHC through regulating the miR-1247-5p-FOXO3 axis 65 . Interestingly, the crucial role of RCD-related abnormally expressed lncRNAs in monitoring and promoting the development and progression of LIHC is drawing growing interest.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Another study revealed that LINC01977 accelerated LIHC progression by inhibiting Notch2 ubiquitination and depletion, suggesting that LINC01977 could be a potential biomarker and therapeutic target for LIHC patients 63 . Similarly, Sun et al indicated that LINC01124 played a tumor-promoting role in LIHC through regulating the miR-1247-5p-FOXO3 axis 65 . Interestingly, the crucial role of RCD-related abnormally expressed lncRNAs in monitoring and promoting the development and progression of LIHC is drawing growing interest.…”
Section: Discussionmentioning
confidence: 96%
“…Emerging research highlights critical roles of lncRNAs to the LIHC development and progression 63 65 . Recently, Chi et al found that the lncRNA PTOV1-AS1 is up-regulation in LIHC and associated with patients’ prognosis and sorafenib resistance 64 .…”
Section: Discussionmentioning
confidence: 99%
“…Expression analysis, TRAP assay and dual luciferase reporter assay were used to verify that miR-1247-5p was the target gene of circATIC. MiR-1247-5p plays a tumor suppressor role in multiple cancers 27 , 29 , 66 . Our studies validated the significant decrease of miR-1247-5p in 52 BLca tissues compared to normal tissues, leading to enhanced proliferation, migration and invasion of BLca cells via targeting Regulator of chromosome condensation 2 (RCC2).…”
Section: Discussionmentioning
confidence: 99%